Modest Challenges for the Fields of Human Service Administration and Social Policy Research and Practice. Issue 4 (8th August 2019) - Hoefer, Richard
ABSTRACT: Four "Modest Challenges" of importance to scholars and practitioners in human service administration and social policy research are identified and discussed. They are: (1) to more completely identify competencies for social work administration and social policy and which do not acknowledge their dual natures; (2) promote engagement and inclusivity in human service organizations; (3) improve human service pay and equity: and (4) decide whether to engage in advocacy or not. Suggestions for solving these modest challenges include broadening our concepts of both administration and social policy with additional related competencies and concomitant changes in social work curriculum; moving toward a strong inclusivity paradigm within social work practice and academia; supporting NASW efforts for higher pay and greater equity; and aggressively embracing the skills and mindset of advocacy. Successfully addressing these modest challenges lays the foundation for more effective organizations and greater opportunities to solve grander challenges.